2018
DOI: 10.1080/10903127.2017.1399181
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis Of Mental Health-Related Presentations To Emergency Medical Services

Abstract: Mental health-related cases represent one in ten EMS attendances in Victoria. A large proportion of mental health presentations receive little intervention by EMS, and could benefit from community-based services provided by mental health clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 12 publications
5
66
1
2
Order By: Relevance
“…Not surprisingly, no disease (A97) was a common code in the non-conveyance group, as was acute alcohol abuse (P16), as was found earlier in Finland [6]. Our study showed that patients in the conveyed group were more likely to suffer mental problems (P29), which is the same result as in previous studies [41,42]. This is surprising, because one study found that psychiatric patients rarely need any treatment [36].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Not surprisingly, no disease (A97) was a common code in the non-conveyance group, as was acute alcohol abuse (P16), as was found earlier in Finland [6]. Our study showed that patients in the conveyed group were more likely to suffer mental problems (P29), which is the same result as in previous studies [41,42]. This is surprising, because one study found that psychiatric patients rarely need any treatment [36].…”
Section: Discussionsupporting
confidence: 81%
“…This is surprising, because one study found that psychiatric patients rarely need any treatment [36]. On the other hand, there is evidence that EMS units often lack the skills required to manage these patients [41]. However, another study found a contrary result, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings reiterate broader calls for improving the quality of ambulance care for people presenting with mental health and/or AOD issues . A range of measures could be included to achieve this, including an educational approach to address potential skills gaps around communication.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, paramedics report that attending mental health and/or AOD presentations comprises a significant proportion of their workload . Australian studies have shown that between 10% and 20% of ambulance presentations are related to mental health and/or AOD concerns . Similar to stigmatizing attitudes documented in the general population and amongst some health professional groups, research indicates that some paramedics display negative attitudes towards people who present with mental health and/or AOD problems .…”
Section: Introductionmentioning
confidence: 99%
“…Australian studies with age‐breakdowns have been undertaken at state level, particularly Victoria and NSW . Nationally, ED data by age group using a narrow definition of MH diagnoses (ICD‐10‐AM F00 to F99 as the primary diagnosis, MH dx ), have been reported annually by the Australian Institute of Health and Welfare (AIHW) for 2004–05 to 2016–17, but no trends have been assessed.…”
Section: Introductionmentioning
confidence: 99%